EFL Senior High School Students' Perspectives on Using Social Media Platforms for English Vocabulary Acquisition - Dilla Hilda Rahayu; Paulina Novarita; Riki Ruswandi (FKIP - Universitas Riau, 2026)
This study was motivated by the increasing use of social media platforms as informal learning resources for English vocabulary acquisition among EFL students. Although social media is widely used for educational purposes, students' perspectives, learning experiences, and the features supporting vocabulary acquisition require further exploration. Therefore, this study investigated EFL senior high school students' perspectives, challenges, and perceived beneficial features of using social media platforms for English vocabulary acquisition outside the classroom. This study employed a qualitative case study design involving approximately 300 eleventh-grade students at SMAN 1 Banjaran, West Java, Indonesia. Data were collected through a screening questionnaire completed by 80 students, a main questionnaire administered to 25 purposively selected participants, and semi-structured interviews with five participants selected through maximum variation sampling. The findings revealed that students generally perceived TikTok and YouTube as engaging, accessible, and contextual platforms for vocabulary acquisition. Features such as subtitles, translation tools, audiovisual content, and example sentences facilitated vocabulary learning, whereas distractions, fast-paced content, limited feedback, and inconsistent content quality remained major challenges.